Was für ein Buch hat Asconius eigentlich geschrieben? Zur Frage nach den Zielen und Methoden des antiken Kommentars zu Ciceros Reden - Chrustaljow, Wjatscheslaw K. (Hyperboreus, 2020)
The author examines the aims and methods of the commentary on Cicero’s speeches written by the Roman scholar Q. Asconius Pedianus in the mid-ﬁrst century AD. In the ﬁrst part of the article a brief sketch of Asconius’ life is given, as far as it can be reconstructed from the available evidence. In the second part the author reviews the current discussion on the problem of Asconius’ aims and criticizes the hypothesis posed recently by C. Bishop who assumes that one of the principal intentions of Asconius’ commentary was to defend Cicero’s reputation from attacks of his detractors. The additional arguments are provided to reinforce the alternative view that Asconius wrote his work as a schoolbook for rhetorical schools. In the ﬁnal part of the article the author discusses the question of Asconius’ attitude towards Cicero and comes to conclusion that his appraisal of Cicero’s qualities as orator and statesman is favourable and reverent.